Study of Diamagnetism in Uranyl Complexes of Some Schiff Bases - Dodwad, S.S.; Arti S. Sawant, Mrs. (Asian Journal of Chemistry, 2010)
Uranyl complexes of Schiff bases obtained by condensing 2-hydroxy-1-naphthaldehyde or salicylaldehyde with aromatic amines have been isolated and characterised. The complexes have the formula [M(LH)2(NO3)2] where M = UO2 and LH = Schiff base. The magnetic susceptibilities of these complexes have been measured on Gouy balance. These values have been compared with the computed ones, obtained by adding the molar susceptibilities of the components, assuming strict additivity. The deviations between the observed and computed values of molar magnetic susceptibility have been discussed in the light of Van Vleck's equation for molar susceptibility of polyatomic molecules.